An Efficient Clustered Regularly Interspaced Short Palindromic Repeat (CRISPR)/CRISPR-Associated Protein 9 Mutagenesis System for Oil Palm (Elaeis guineensis) - Yeap, Wan-Chin; Norkhairunnisa Che Mohd Khan,; Norfadzilah Jamalludin,; Muad, Muhammad Rashdan; Appleton, David Ross; Harikrishna Kulaveerasingam, (Frontiers in Plant Science, 2021)
The clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR-associated protein 9 (Cas9) system has emerged as a powerful tool for precise editing of plant genomes for crop improvement. Rapid in vitro methods for determination of guide RNA (gRNA) cleavage efficiency and an efficient DNA delivery system are essential for gene editing. However, we lack an efficient gene editing system for palm species. Herein, we describe the development of a transient oil palm protoplast assay to rapidly evaluate the cleavage efficiency of CRISPR/Cas9 mutagenesis and for the generation of stable transformed oil palms using biolistic particle bombardment in immature embryos. Using the phytoene desaturase (EgPDS) gene, we found cleavage frequency of up to 25.49% in electro-transfected protoplast, which enable the production of transgenic oil palm shoots exhibiting chimeric albino phenotypes as a result of DNA insertions, deletions (InDels) and nucleotide substitutions, with a mutation efficiency of 62.5-83.33%. We further validated the mutagenesis efficiency and specificity of the CRIPSR/Cas9 system in oil palm by targeting brassinosteroid-insensitive 1 (EgBRI1) gene, which resulted in nucleotide substitutions in EgBRI1 with premature necrosis phenotype in oil palm transgenic shoots and stunted phenotype resulted from DNA InDels. Taken together, our results showed that effective and efficient editing of genes by CRISPR/Cas9 system can be achieved in oil palm by optimizing the selection of efficient gRNA and DNA delivery method. This newly designed strategy will enable new routes for genetic improvement in oil palm and related species.